2022
DOI: 10.21597/jist.1065147
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Amoxicillin Trihydrate Purified Using Washing Method by Taguchi Method

Abstract: Saf bir kristal ürün elde etmek için tekrar tekrar uygulanan kristalizasyon basamakları veya farklı kimyasallara başvurulması, bitmiş ürünün veriminde farklı sorunlara neden olabilir. Bundan dolayı, kristal ağın içerisindeki safsızlıklar, ana ürünü etkilemeden uzaklaştırılmalıdır. Bu çalışmada, Amoksisilin trihidrat (Amct) ve safsızlık olarak 4-hidroksifenilglisin (4-HPG) kullanılmıştır. Amct kristal kafesinden, safsızlık olarak 4-HPG’nin yıkama yöntemleri kullanılarak uzaklaştırılması gösterilmiştir. Ayrıca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To standardize the crystallization process, a 100 mL Büchner glass funnel and two 100 mL jacketed reactors were utilized in the experiments. The Büchner glass funnel employed in this study was specially designed to minimize crystal loss, and all experiments were conducted using this apparatus. , The process temperature and the temperatures of all solutions used were adjusted to room temperature. Prior to each experiment, the system was operated under the specified conditions for 30 min to attain a stable state.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To standardize the crystallization process, a 100 mL Büchner glass funnel and two 100 mL jacketed reactors were utilized in the experiments. The Büchner glass funnel employed in this study was specially designed to minimize crystal loss, and all experiments were conducted using this apparatus. , The process temperature and the temperatures of all solutions used were adjusted to room temperature. Prior to each experiment, the system was operated under the specified conditions for 30 min to attain a stable state.…”
Section: Methodsmentioning
confidence: 99%
“…The literature predominantly focuses on the adverse impact of introducing impurities structurally similar to the primary molecule on crystal growth. The separation of AMCT from its own degradation products, in particular, has garnered emphasis. In their investigation, Feng et al demonstrated that an increase in the concentration of degradation products leads to a decrease in AMCT nucleation . In another study, Ghassempur et al detailed the integration of impurities into the AMCT crystal lattice and its consequent impact on the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation